The power of consumers in controlling the price of goods: an analysis from the perspective of consumer sovereignty and modern market mechanisms - Abu Bakar, Bazri; Sardan, Mohd Azim; Mohamed Abdul Kadir, Juliana; Ali@Saip, Azman (Universiti Teknologi MARA, Johor, 2025)
Classical economic theory suggests that prices are determined when demand meets supply, portraying consumers as passive price takers. However, this view no longer reflects modern realities. Consumers today are active players, capable of influencing prices through individual and collective actions. This shift is driven by technology, increased awareness of consumer rights, and globalization that provides wider choices. This article explores the concept of consumer power in price control, focusing on consumer sovereignty and available mechanisms for action. The concept of consumer sovereignty is a fundamental doctrine in economics which states that in a market economy, the consumer is "king." The desires and needs of consumers are the primary drivers of production decisions and pricing (Sirgy et al., 2021). According to this theory, firms that fail to meet consumer demands at a price deemed reasonable will lose customers to their competitors